(untitled) (Bangladesh Journal of Pharmacology, 2013)
Our study investigated the role of delta-like 1 (DLL1) in multi-drug resistance of small cell lung cancer. Differentially expressed genes were detected in resistant small cell lung cancer H69AR cells and sensitive small cell lung cancer H69 cells by microarray. DLL1 expression in H69 cells and H69AR cells was further confirmed by RT-PCR and Western blot assay. eGFP-RNA was employed to up-regulate DDL1 expressing in H69AR cells (H69AR-eGFP-DLL1) by transfection. These cells were treated with different chemotherapeutics (ADM, DDP, and VP-16). Cell viability was detected. Cell cycle and apoptosis rate were determined. The DLL1 expression was significantly decreased in H69AR cells when compared with H69 cells. Over-expression of DLL1 increased the sensitivity of H69AR cells to chemotherapy, which was characterized by increase in apoptosis and arrest in G0/G1 phase. Our results demonstrate that up-regulation of DLL1 expression in small cell lung cancer cells may increase their sensitivity to chemotherapeutic agents.